Persepsi “Kafir” pada Muslim dan Non-Muslim: Konteks, Penggunaan, dan Komunikasi Partisipatif - Wahid, Abdul (Universitas Brawijaya, 2020)
The use of religious terms such as 'kafir' is seen as a form of radicalism because it discriminates against other groups; both Muslim and non-Muslim groups. Radicalism can encourage intolerant behavior and violence. In political contexts such as elections, mass groups often use these calls to discriminate against other groups that are considered to have different views. This study was conducted to find out how